(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Despite abundant anti-arthritic therapies, there always remains an opportunity to identify novel drugs as well as targets. One such emerging drug Capparis aphylla Roth. acting on inflammatory cascades. This study was planned to investigate the effect of C. aphylla Roth. on inflammatory cascade in rheumatoid arthritis induced in wistar albino rats. The rheumatoid arthritis was induced by injection of 0.2 mL complete Freund’s adjuvant. The animals were randomized into six groups receiving either vehicle (control), injection of 0.2 mL complete Freund’s adjuvant (model) or treatments (indomethacin 100 mg/kg and methanolic extract of C. aphylla Roth. 190, 240, 300 mg/kg) for 21 days. Various hemodynamic parameters, anti-inflammatory parameters, and x-ray and histopathology of synovial joints were carried out. Paw volume, body weight, arthritic index, ESR, RF, CRP, A/G ratio estimated. Treatment with methanolic extract of C. aphylla Roth. Significantly prevented the rise in body weight, serum A/G ratio and increased arthritic index, paw volume, ESR, RF, CRP. The normal architecture of synovial joints was preserved in histopathological analysis by methanolic extract of C. aphylla Roth. treatment. Furthermore, the prevention of damage in joints carried out by methanolic extract of C. aphylla Roth. Altogether, methanolic extract of C. aphylla Roth. prevented architecture and functions of joints by augmenting the inflammation in complete freund’s adjuvant rats. Such promising effects are attributed to inflammation by novel herbal drug C. aphylla Roth.